IMMU-08. MODELING UPFRONT GLIOBLASTOMA SURGICAL RESECTION AND STEROID USE REVEALS IMMUNOSUPPRESSIVE CHANGES AND SUGGESTS THAT PERIPHERAL LYMPHOCYTE COUNTS ARE ASSOCIATED WITH TUMOR VOLUME AND PROGNOSIS - Otvos, Balint (Neuro Oncol, 2020)
Glioblastoma (GBM) and its treatment produces systemic immunosuppression, which is being targeted by immunotherapies. However, it remains unclear how surgical resection and steroids specifically in GBM alter the immune system. To further explore this issue, immunocompetent C57Bl/6 mice were intracranially inoculated with syngeneic glioma cells (GL261 and CT-2A) and growth of tumors was evaluated by MRI. Host immune cell populations were analyzed during surgical resection and steroid administration. Mice with surgically resected tumors had a longer median survival compared to mice subjected to tumor biopsies, and had increased bone marrow sequestration of both CD4 and CD8 T cells with corresponding decreased blood lymphocytes. Furthermore, physiologic doses of dexamethasone administered perioperatively decreased tumor edema, but increased the number and proliferative capacity of both marrow and circulating MDSCs while generating no survival benefit. Independent of therapy or dexamethasone, intracranial tumor volume correlated linearly with decreased CD4 and CD8 T cells in peripheral blood, and increased T cell sequestration within the bone marrow. We validated these parameters in steroid-naïve newly diagnosed GBM patients and observed decreased lymphocytes correlated linearly with increased tumor volume. When initial lymphocyte counts in both steroid-naïve and steroid-administered patients were used in univariate and multivariate models predicting progression-free survival and overall survival, decreased initial lymphocyte counts were an independent predictor of decreased progression free survival and decreased overall survival, with steroid use and initial tumor size falling out of significance during stepwise selection. Taken together, tumor volume is linearly correlated with marrow sequestration of lymphoid cells, but both surgery and steroid administration further suppress active immune responses along lymphoid and myeloid lineages. Furthermore, decreasing peripheral lymphocyte counts at diagnosis of GBM indicate an immune system less able to mount responses to the tumor and portent a worse progression free and overall survival.